Tuning the functionality of graphene oxide for adsorption and sensing applications - Aruna Unnikrishnan (Department of Physics, University of Calicut, 2025)
Graphene oxide (GO), a versatile two-dimensional material, exhibits unique properties due to its oxygen-containing functional groups, making it an ideal candidate for adsorption and sensing applications. This thesis focuses on systematically tuning the functionality of GO through various modifications to enhance its performance in these domains. The research is divided into five working chapters, each exploring a distinct modification strategy. The first chapter investigates the chemical modification of GO using sodium hydroxide (NaOH). By varying the NaOH concentration, significant alterations in the oxygen functional groups and their distribution within GO were observed. Our study identified a threshold NaOH concentration of 5.45:1 (NaOH:GO by weight) as critical for reducing graphene oxide (GO), as evidenced by enhanced π-π* transitions in UV- visible spectra and an increased ID/IG ratio in Raman analysis. We established that UV-visible absorbance maxima, rather than peak shifts, serve as a more reliable indicator of GO reduction. Unlike with NaBH 4, where pH and absorbance maxima followed similar trends, NaOH reduction showed distinct behaviour, with absorbance maxima proving more indicative of the reduction pathway. This conclusion was further validated by Raman analysis, confirming that pH does not play a decisive role in GO reduction. This study provides a foundation for optimizing GO's structure to meet specific application needs. In the second chapter, GO was combined with activated carbon to form a composite material in simple step aimed at enhancing its adsorption capabilities. GOAC demonstrated exceptional efficiency in removing different dyes like methylene blue, rhodamine b, congo red, their mixtures and antibiotics - ciprofloxacin. We evaluated GOACs adsorption kinetics and found that these reactions followed pseudo second order kinetics and also proposed corresponding mechanisms for integration. Such performance addresses critical challenges in industrial wastewater treatment showcasing the synergistic interaction between GO and activated carbon. The third chapter examines the formation of a reduced graphene oxide-gold nanoparticle (rGO-Au) composite for sensing applications. This composite wasevaluated for uric acid detection using UV-visible spectroscopy, where a fivefold enhancement in sensitivity was observed compared to GO or gold nanoparticles alone. The rGO-Au composite showed excellent performance within physiologically relevant detection ranges, emphasizing its potential for biosensing applications in medical diagnostics and environmental monitoring. In the fourth chapter, the effect of synthesis time on GO’s properties was systematically studied. GO samples prepared with synthesis durations of 2, 4, 8, and 18 hours, designated as GO2Hr, GO4Hr, GO8Hr, and GO18Hr, were evaluated for adsorption and sensing applications. Adsorption studies revealed that GO2Hr exhibited superior performance for methylene blue and naphthalene in a short duration. For MB adsorption, we achieved the highest adsorption capacity of 1285mg/g at the best time of 4 minutes. These samples were also tested for ascorbic acid sensing, underscoring the importance of synthesis time as a key parameter in tailoring GO's functionality. The final chapter explores the integration of GO into a 3D melamine sponge (MSGO) to create a composite structure for simultaneous dye removal and oil-water separation. MSGO samples derived from time-varied GO synthesis demonstrated excellent performance, particularly in saline conditions. MSGO2 showed exceptional adsorption kinetics and efficient oil-water separation for different set of oils in tap water and sea water, making it a promising material for real-world environmental remediation. In conclusion, this thesis presents a systematic approach to modifying GO and its composites to optimize their functionality for adsorption and sensing applications. The findings contribute significantly to the understanding of GO’s potential as a multifunctional material and offer practical solutions for challenges in environmental and biosensing technologies.
Keywords: Graphene oxide; adsorption; sensing; oil water separation; methylene blue; rhodamine b; congo red; ciprofloxacin; naphthalene; ascorbic acid; uric acid; adsorption kinetics